Optimization planted area to maximize production of palm fruit using goal programming (GP) / Wan Nurshazelin Wan Shahidan ... [et al.] - Wan Shahidan, Wan Nurshazelin; Nadzri, Nur Atikah; Jusoh@Hussain, Nordianah; Muhammat Pazil, Nur Syuhada; Sarkam, Saida Farhanah (Universiti Teknologi MARA, Perlis, 2019)
Malaysia is the second largest palm oil production in the world. Malaysian Federal Land Consolidation and Rehabilitation (FELCRA) is an important agency to nurture local palm oil industry by involving local community. However, in 2017, FELCRA Seberang Perak at the Northern Malaysia reported a decreasing of 5% palm oil production as compared to the previous year. FELCRA Seberang Perak has four palm planted areas yet the administrators had not fully utilized the areas for optimum production. Thus, the study applied goal programming model in order to find the optimal palm planted area at FELCRA Seberang Perak. The study has three-fold objectives, which are: 1) to maximize each planted area; 2) to maximize the number of palm trees; and 3) to maximize the palm fruit production for each area. The study analysed data using QM for Window version 5.3. The findings show that the optimal planted area for FELCRA Seberang Perak is 5,662.80 hectares while the maximum number of palm trees are 845,829 which may annually produce 224,120.20 tonnes of palm oil. The result of the study can be applied by FELCRA Seberang Perak's administrators as to increase its palm oil productivity at the most optimum level as well as to spur the Malaysian economy in the global commodity market